Quantificação e caracterização de microplásticos na atmosfera de São Carlos – SP - Ferraz, Gabriel Marcondes (Universidade Federal de São Carlos, 2022)
With the rampant use of plastics, combined with the annual increase in its production, a large generation of waste is often incorrectly disposed of, resulting in plastic pollution in the environment, including macro, micro, and nanoplastic pollution. Therefore, the present work aimed to quantify and characterize physical and chemically atmospheric MPs in the city of São Carlos. For this purpose, samples containing MPs were collected, using active and/or passive sampling, indoors and outdoors Doutor Álvaro Guião State School. In the outdoors, the mean concentrations of MPs in the samples were 0.82 ± 0.73 fragments m-3 using an active sampler, and 38.69 ± 20.89 fragments m-2 day-1 and 1.26 ± 0, 88 fibers m-2 day-1 in the dry season, and 25.63 ± 25.51 fragments m-2 day-1 and 0.29 ± 0.51 fibers m-2 day-1 in the rainy season using a passive sampler. Indoors, using passive sampling, the mean concentration was 39.84 ± 22.43 fragments m-2 day-1 and 18.08 ± 6.09 fibers m-2 day-1 in the dry period, and 10.52 ± 17.95 fragments m-2 day-1 and 7.56 ± 4.55 fibers m-2 day-1 in the rainy season. Statistically significant seasonal variation was verified indoors for both morphologies. In addition, fiber concentrations, in the dry and rainy periods, were higher indoors compared to outdoors. The fragments determined in the samples were smaller than the fibers regardless of the type of sampling and whether in an outdoor or indoor ambient. The colors were variable in both morphologies. The built prediction model, the PLS-DA model, for the 12 classes (PS, PC, PET, PLA, Polyester, PP, PU, PE, PLA, Ethylene-Octene,, EVA and MCE Filter) with 11 Latent Variables allowed the explanation of 88.48% of the variance found, with an overall Mean Squared Cross Validation Error of 7.36 ± 6.16%. The majority component of the MPs was Polyester/PET, determined in 100% of the samples. Its proportion ranged from 29 to 100%, followed by EVA (0 to 57%), PE (0 to, 14%) and Ethylene-Octene (0 to 5%). The MPs ubiquity has been demonstrated, as well as the importance of more studies on atmospheric MPs and their implications on the environment and health.
Quantification and characterization of microplastics in the atmosphere of São Carlos – SP
Keywords: Microplásticos atmosféricos; Poluição microplástica; Contaminação microplástica; Fontes de emissão de microplásticos; Atmospheric Microplastics; Microplastics pollution; Microplastics contamination; Microplastics emission sources; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA